A Cross-Sectional Study on Factors Related to Status of Meconium Stained Liquor Labour Patients Attended at Tertiary Level Hospital in Dhaka, Bangladesh - Sultana, Shanjida; Ferdows, Jannat Ara; Tasmin, Khandaker Shehneela; Susan, Zobaida Sultana; Akter, Taslima (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Meconium-stained liquor during labor is a common almost daily encountered problem. Objective: The purpose of the study was to find out factors related to meconium-stained liquor affecting during labor. Methodology: This is a cross-sectional, hospital-based observational study conducted in the Department of Obs & Gyne, Shaheed Suhrawardy Medical College Hospital, Dhaka. The cases with single, term pregnancy with cephalic presentation presented with meconium-stained liquor was selected. All the cases willingly participated in this study. Data collection and fetal assessment was conducted in the labor room. The meconium-stained liquor was clinically and completely in a structured questionnaire according to the events that happened pre and post-delivery including neonatal outcome data. Data was analyzed by computer using the SPSS program (Statistical Package of Social Sciences), version-22, and p value <0.05 considered as statistically significant. Result: The mean age of the study group was 32.3±6.4 years. The Level of education of the study population, illiterate 12.0%, primary school 21.0%, majority SSC 33.0%, HSC 20.0% and graduation 14.0% and the occupation of the study patients mostly housewife 65.0%, least service.10.0%, business 14.0% and other professions 11.0% and mean gestational week was 40.12±1.43. Conclusion: The meconium-stained liquor labour is a serious condition and related with some factors which can be addressed by these factors and the safety of maternal and fetal outcomes. J Shaheed Suhrawardy Med Coll 2021; 13(2): 109-112